Financial Risk Comparison Between New Energy Vehicle Enterprises: Taking BYD and Tesla (China) as Examples - Lin, Xuan (International Journal of Global Economics and Management, 2024)
This article provides an in-depth analysis of the development of the new energy vehicle industry, particularly the competitive position of BYD and Tesla (China) in the global new energy vehicle market. The article begins by introducing the rapid development of the new energy vehicle industry, followed by an examination of the financial performance and risk management strategies of BYD and Tesla, as well as their strategies and recommendations for addressing industry challenges. Through comparative analysis, the article aims to reveal the trends in the new energy vehicle industry and the financial strategies that companies should adopt to achieve long-term stable growth.